Tren Penerbitan Mushaf dalam Komodifikasi al-Qur’ān di Indonesia - Eva Nugraha (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2015)
a sacred entity, muṣḥaf of the Qur’ān has long been the commodified objects. In Indonesia, it has been over150 years published and marketed withits various forms. In the last 10 years,Qur’ānic publishing phenomenon in Indonesia has developedin the new formandappearance, both in terms of conten tanda ccompanying theme. Fromthis background, this paperwants toexaminethe question: howtheQur’ānic publisherspresent,publishandmarket the product of the Qur’ānic muṣḥaf,whicheventuallybecamea trendinpublishingthe Qur’āninIndonesia?